2015
DOI: 10.1007/s10815-015-0466-6
|View full text |Cite
|
Sign up to set email alerts
|

Systemic oxidative stress could predict assisted reproductive technique outcome

Abstract: Purpose Previous studies have indicated that OxS (oxidative stress) may appear as a possible reason for poor ART outcome. Our aim was to study OxS levels in both partners of couples seeking Assisted reproduction Technology (ART). Methods Altogether 79 couples were recruited. Oxidative DNA damage (8-OHdG) and lipid peroxidation (8-EPI) were measured, and clinical background and ART outcomes were recorded. Results Both OxS markers accurately reflected clincal conditions with prominent negative effects attributab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…The reduced ROS in the lower layer relative to the unwashed samples strongly suggests that the treatment of semen by DGC does not expose motile sperm to oxidative stress. Several studies have reported that excessive ROS levels in washed semen are negatively correlated with fertilization and pregnancy rates [Zorn et al 2003;Das et al 2008;Ahelik et al 2015]. Furthermore, ROS levels were higher in unwashed semen samples of couples that did not achieve pregnancy compared to those that did [Yumura et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced ROS in the lower layer relative to the unwashed samples strongly suggests that the treatment of semen by DGC does not expose motile sperm to oxidative stress. Several studies have reported that excessive ROS levels in washed semen are negatively correlated with fertilization and pregnancy rates [Zorn et al 2003;Das et al 2008;Ahelik et al 2015]. Furthermore, ROS levels were higher in unwashed semen samples of couples that did not achieve pregnancy compared to those that did [Yumura et al 2009].…”
Section: Discussionmentioning
confidence: 99%
“…All these events negatively affect sperm parameters, 9‐15 male fertility, 12 and pregnancy outcome of their partners. Clinically, several studies have demonstrated that OS in human semen resulted in significantly poor assisted reproductive technology (ART) outcomes, such as lower fertilization rates, arrest of embryonic development, implantation failure, recurrent pregnancy loss, and lower live birth rates 16‐18 . Agarwal et al proposed the term and concept of “Male Oxidative Stress Infertility (MOSI)”, 19 and it has been determined that there are many patients with MOSI among those who were previously classified as having idiopathic male infertility 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, several studies have demonstrated that OS in human semen resulted in significantly poor assisted reproductive technology (ART) outcomes, such as lower fertilization rates, arrest of embryonic development, implantation failure, recurrent pregnancy loss, and lower live birth rates. [16][17][18] Agarwal et al proposed the term and concept of "Male Oxidative Stress Infertility (MOSI)", 19 and it has been determined that there are many patients with MOSI among those who were previously classified as having idiopathic male infertility. 19 Understanding the effects of ROS on male fertile capacity, measuring OS accurately, and treating patients based on their pathophysiologies will contribute to improving male infertility outcomes.…”
mentioning
confidence: 99%
“…Endometriosis is a disease associated with elevated ROS, both in the follicular environment and systemically1415161718. It is also known that ROS causes DNA damage19.…”
mentioning
confidence: 99%